Doppler ultrasound predicts successful discontinuation of biological DMARDs in rheumatoid arthritis patients in clinical remission. (20th March 2021) - Terslev, Lene; Brahe, Cecilie Heegaard; Hetland, Merete Lund; Georgiadis, Stylianos; Ellegaard, Karen; Juul, Lars; Huynh, Tuan; Døhn, Uffe Møller; Fana, Viktoria; Møller, Torsten; Krabbe, Simon; Ørnbjerg, Lykke Midtbøll; et al.
Abstract: Objective: To assess the ability of ultrasound to predict successful tapering and successful discontinuation of biological DMARDs (bDMARDs) at the 2-year follow-up in RA patients in sustained remission. Methods: Patients in sustained remission (DAS28-CRP ≤ 2.6) and with no radiographic progression the previous year tapered bDMARDs according to a standardized regime. A total of 119 of these patients were included in this ultrasound substudy. At baseline, clinical assessment, MRI, X-ray and ultrasound of 24 joints were performed. Ultrasound-detected synovitis was defined and scored 0–3 using the OMERACT scoring system at the joint level for both grey-scale and Doppler activity. Sum scores for each ultrasound modality were calculated for 24 joints at the patient level. The final state of treatment was assessed after 2 years. The predictive value of ultrasound measures for successful tapering and discontinuation at the 2-year follow-up was assessed via logistic regression analyses. Results: Negative IgM-RF [odds ratio (OR) = 0.29, 95% CI: 0.10–0.85; P = 0.024] and lower Doppler sum score of 24 joints (OR = 0.44, 95% CI: 0.15, 0.87; P = 0.014) were independent predictors for successful discontinuation of bDMARDs at the 2-year follow-up. The predictive value of the Doppler sum score was independent of MRI findings. Previous numbers of bDMARDs were predictive of successful tapering (OR = 0.58, 95% CI: 0.35, 0.91; P = 0.018), whereas ultrasound was not. Clinical parameters were not predictive of successful tapering/discontinuation. Conclusion: Doppler sum score was an independent predictor for successful discontinuation of bDMARDs at the 2-year follow-up—the odds for achieving successful discontinuation decreased by 56% per one-unit increase in Doppler sum score. Ultrasound could not predict successful tapering.